River Reorganization Affects Populations of Dwarf Cichlid Species (Apistogramma Genus) in the Lower Negro River, Brazil - Leitão, Carolina Sousa de Sá; Souza, Érica M. S.; Santos, Carlos H. A.; Val, Pedro; Val, Adalberto L.; Almeida-Val, Vera M. F. (Frontiers in Ecology and Evolution, 2021)
Alterations, such as drainage network reorganization, in the landscape in the Amazon basin influence the distribution range and connectivity of aquatic biota and, therefore, their evolution. River capture is a geomorphic mechanism of network reorganization by which a basin captures large portions of the network of a neighbouring basin, thus creating a barrier against species dispersal. In this study, the influence of river capture on the genetic differentiation and structuring of two dwarf cichlids species (Apistogramma pertensis and Apistogramma gephyra) is investigated in two tributaries of the lower Negro River. The analysis of 11 loci microsatellite and three mitochondrial DNA genes (Cytochrome b, Citochrome c Oxidase subunit I and 16S ribosomal RNA) confirmed the populational isolation of two dwarf cichlids species, suggesting that they represent evolutionary significant units (ESU) that have been isolated - probably due to the river capture event. The paleovalley that resulted from the river capture is therefore an important physical barrier that separates the populations of the Cuieiras and Tarumã-Mirim Rivers. The findings herein provide evidence of a mechanistic link between the isolation and differentiation of fish populations and the drainage evolution of the Amazon basin, and indicate that the dynamic geological history of the region has promoted species diversification. The process described here partially explains the high diversity in the genus Apistogramma and the information obtained is beneficial to conservation programs.